2015
DOI: 10.1128/iai.00168-15
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Biological Characterization of Babesia microti Apical Membrane Antigen 1

Abstract: eThe intraerythrocytic apicomplexan Babesia microti, the primary causative agent of human babesiosis, is a major public health concern in the United States and elsewhere. Apicomplexans utilize a multiprotein complex that includes a type I membrane protein called apical membrane antigen 1 (AMA1) to invade host cells. We have isolated the full-length B. microti AMA1 (BmAMA1) gene and determined its nucleotide sequence, as well as the amino acid sequence of the AMA1 protein. This protein contains an N-terminal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…divergens AMA1 antibodies (24) and ϳ80% in vitro inhibition of B. microti has been achieved with anti-B. microti AMA1 antibodies (31), confirming that AMA1 is certainly a key player in Babesia invasion. However, in a controlled human malaria challenge trial, the P. falciparum AMA1 (PfAMA1) vaccine conferred little protection even against the homologous parasite ( [62][63][64], showing that AMA1 alone may not be suitable as a candidate on its own.…”
Section: Figmentioning
confidence: 64%
See 1 more Smart Citation
“…divergens AMA1 antibodies (24) and ϳ80% in vitro inhibition of B. microti has been achieved with anti-B. microti AMA1 antibodies (31), confirming that AMA1 is certainly a key player in Babesia invasion. However, in a controlled human malaria challenge trial, the P. falciparum AMA1 (PfAMA1) vaccine conferred little protection even against the homologous parasite ( [62][63][64], showing that AMA1 alone may not be suitable as a candidate on its own.…”
Section: Figmentioning
confidence: 64%
“…In these parasites, part of the trigger that commits a parasite to invasion is the formation of the moving junction (MJ), key components of which are apical membrane antigen 1 (AMA1), which is initially stored in the micronemes, binding with rhoptry neck protein 2 (RON2) (30). The AMA1 proteins of both B. divergens (24) and B. microti (31) have been identified, and their general structures show high degrees of homology to those of the AMA1 proteins from other parasites. Here we report on the identification and characterization of the RON2 proteins from both major species involved in human babesiosis, B. divergens and B. microti, allowing further characterization of their role in invasion in comparison with the roles of the RON2 homologs of other apicomplexan parasites.…”
mentioning
confidence: 99%
“…Nonetheless, previous studies have shown a significant difference between in vitro culture and in vivo environment. For example, it has been reported that the antiserum raised against BmAMA1 can effectively block the invasion of B. microti into host cells in an in vitro culture environment (Moitra et al, 2015), but the mice immunized with rBmAMA1 did not show any significant protection after B. microti challenge (Wang et al, 2017). Therefore, more evidence needs to be gathered to support that BmSA1 is important for the invasion of B. microti into host cells in an in vivo environment.…”
Section: Discussionmentioning
confidence: 99%
“…Infected mouse blood was obtained from the Kumar laboratory (FDA/CBER/DETTD, Silver Spring, MD) and detailed procedures were described elsewhere (Moitra et al, 2015). Briefly, DBA/2 mice are injected with a blood sample containing intraerythrocytic Babesia microti (ATCC PRA-99), allowed to infect until microscopic observation of a blood sample reveals 10–20% parasitemia.…”
Section: Methodsmentioning
confidence: 99%